Shifting Perilaku Manusia: Peralihan dari Interaksi Fisik ke Digital; Digital Society & Networked Individualism - Fadiah Aisyah; Cory Vidiati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The phenomenon of the shift in human behavior from physical interaction to digital interaction marks the emergence of a digital society and networked individualism, in which individuals construct their identities, social networks, and economic activities within increasingly personal yet widely connected digital spaces. This study employs a library research method with a literature ratio approach to examine the relationship between digital behavior and Islamic values in the context of the digital economy. The findings indicate that digitalization significantly transforms human social interaction patterns, morality, and spirituality, thereby necessitating the internalization of Islamic values such as shiddiq (honesty), amanah (trustworthiness), adl (justice), ihsan (benevolence), tawazun (balance), and haya (modesty) in every digital activity. These values serve as ethical guidelines to direct digital behavior toward justice, civility, and social benefit. Thus, integrating Islamic principles into digital practices forms a crucial foundation for establishing an ethical, inclusive, and welfare-oriented digital society.